THE HUMAN CAPITAL MANAGEMENT IN THE CONDITIONS OF INFORMATION SOCIETY - Svetlana V. Panyukova; Alexey M. Gostin; Svetlana V. Avilkina (Статистика и экономика)
In the article an approach to introduction in the human capital management of new information technologies is offered. The analysis of a current state of the human capital in Russia, its mobility is carried out. Results of using social networks services for creation of a web portfolio of the student and the teacher in higher education institution are presented. The main directions of using cloudy technologies in Russian human capital management, in the solution of the problems connected with graduate’s employment are formulated.